2006
DOI: 10.1103/physrevd.73.025009
|View full text |Cite
|
Sign up to set email alerts
|

Quantum electrodynamics near a dielectric half-space

Abstract: We determine the photon propagator in the presence of a non-dispersive dielectric half-space and use it to calculate the self-energy of an electron near a dielectric surface.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(61 citation statements)
references
References 16 publications
(32 reference statements)
2
59
0
Order By: Relevance
“…This introduces the additional complication that the reflection coefficient has branch points at k z =±ik , causing the formulas (12) and (13) to become ambiguous. Our method is reliant on the fact that whatever happens above −ik in the lower half of the k z plane does not preclude a contour deformation that allows us to simply pick up the residue at k z =−ik .This inability to deform a contour once damping is introduced has been investigated in detail in [23], where it is concluded that standard derivations of the Lifshitz formula with damping must contain an unspecified inconsistency (a statement reflected by experimental results [24]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This introduces the additional complication that the reflection coefficient has branch points at k z =±ik , causing the formulas (12) and (13) to become ambiguous. Our method is reliant on the fact that whatever happens above −ik in the lower half of the k z plane does not preclude a contour deformation that allows us to simply pick up the residue at k z =−ik .This inability to deform a contour once damping is introduced has been investigated in detail in [23], where it is concluded that standard derivations of the Lifshitz formula with damping must contain an unspecified inconsistency (a statement reflected by experimental results [24]).…”
Section: Resultsmentioning
confidence: 99%
“…However, one can use the Lifshitz theory and write the electromagnetic field as a response to fluctuating noise currents inside the material (see, for example, [18]). The Green's function describing this response involves the reflection coefficients of the surface so that one necessarily ends up with the same formulas (12) and (13), regardless of the specific choice of dielectric function. Proceeding along these lines, we use our formulas to investigate a model in which a restoring force is introduced [19], summarized by the introduction of a new characteristic frequency ω T into the dielectric function:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the present condition is also close to the generalized Coulomb gauge condition considered in Ref. [26]. For the case of non-dissipative and also non-dispersive isotropic media, i.e., for the case of constant dielectric permittivity, a close condition can be obtained.…”
Section: Em-field's Equation In the Temporal Gaugementioning
confidence: 57%